The relationship between subsoil colour and degree of wetness in a suite of soils in the Grabouw district, Western Cape - Van Huyssteen, C. W.(Cornelius Wilhelm) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1995.